2010
DOI: 10.1136/jnis.2009.001933
|View full text |Cite
|
Sign up to set email alerts
|

Intra-arterial abciximab for the treatment of thrombus formation during coil embolization of intracranial aneurysms

Abstract: Thrombus formation during coil embolization of intracranial aneurysms occurred more in women and smokers. Low doses of intra-arterial abciximab may be effective in the thromboembolic complications occurring during endovascular embolization of intracranial aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Most of the thromboembolism reported previously was partially occluded thrombus detected at the coil−parent vessel interface 1 6 8 9 12. However, thromboembolism can develop anywhere during coil embolization, including areas proximal and distal to the aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the thromboembolism reported previously was partially occluded thrombus detected at the coil−parent vessel interface 1 6 8 9 12. However, thromboembolism can develop anywhere during coil embolization, including areas proximal and distal to the aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] The infarction rate among patients receiving rescue therapy ranges between 10% and 40% with higher rates generally seen in studies with postoperative MR imaging [1][2][3][4][5][6][7][8][9][10][11][12][13][14] ( Table 5). In a series of 477 patients with 515 intracranial aneurysms, Ries et al 1 reported that 48 patients (10%) had thromboembolic events; 42 of these patients received rescue therapy with GpIIbIIIa inhibitors, and 1 patient received rescue therapy with recombinant tissue plasminogen activator.…”
Section: Discussionmentioning
confidence: 99%
“…Of the patients who did not receive rescue therapy, 3/5 had infarcts, whereas 31% of patients receiving GpIIbIIIa inhibitor rescue therapy had infarction on computed tomography. Linfante et al 10 demonstrated that ≈10% of patients undergoing endovascular embolization of intracranial aneurysms required intra-arterial GpIIbIIIa inhibitor rescue therapy with an infarct and hemorrhage rate of 0%. Many previous studies that have demonstrated high-infarct rates on postoperative imaging also highlight the fact that many of these infarcts are clinically silent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the collective experience with similar use of intra-arterial abciximab (IAA) or tirofiban shows an average rate of complete recanalization of 73.9 and 67.7%, respectively (table 5) [9,13,14,15,16,17,18,19,20,21,22,23,24]. More studies are warranted in further exploring the efficacy of IAE.…”
Section: Discussionmentioning
confidence: 99%